Analyzing the Impact of Financial Socialization and Social Media Influence on Young Consumers' Behavioral Patterns - Srinija Nekkanti; Aditi Kalani; Mahek Narwani; Rahul Chauhan; Andino Maseleno; Rizal Isnanto (Greenation International Journal of Economics and Accounting, 2023)
This study analyzes the impact of financial socialization and social media influence on young consumers' behavioral patterns, focusing on age and gender differences. Utilizing a quantitative approach, the research examines how technological advancements and social factors shape financial literacy and spending habits among youth. Findings indicate that while age influences engagement with social media and influencers, fundamental financial behaviors like budgeting show minimal variation across age groups. Gender analysis reveals significant differences in price comparison behaviors, suggesting the need for targeted marketing strategies. The study emphasizes the importance of financial literacy education in a digital context and highlights opportunities for further research on cultural influences and evolving consumer behaviors. Overall, the insights gained underscore the critical role of social media and technology in shaping the financial practices of young consumers.